2021
DOI: 10.1002/rth2.12572
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration of vaccine‐induced immune thrombotic thrombocytopenia treated by heparin and platelet transfusion: Insight from functional cytometry and serotonin release assay

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Based on our literature review, LR associated with the COVID-19 vaccine seems rare [ 4 5 ]. Bérezné et al [ 4 ] reported a case of LR that appeared after ChAdOx1 nCoV-19 injection, and Mintz et al [ 12 ] reported another case of LR after the third dose of messenger RNA-1273 SARS-CoV-2 vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on our literature review, LR associated with the COVID-19 vaccine seems rare [ 4 5 ]. Bérezné et al [ 4 ] reported a case of LR that appeared after ChAdOx1 nCoV-19 injection, and Mintz et al [ 12 ] reported another case of LR after the third dose of messenger RNA-1273 SARS-CoV-2 vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our literature review, LR associated with the COVID-19 vaccine seems rare [ 4 5 ]. Bérezné et al [ 4 ] reported a case of LR that appeared after ChAdOx1 nCoV-19 injection, and Mintz et al [ 12 ] reported another case of LR after the third dose of messenger RNA-1273 SARS-CoV-2 vaccine. One case of pernio-like manifestations on both hands with intermittent appearance of an LR-like rash on the legs and another case of livedo racemosa on both thighs were also reported to have occurred after injection of the BNT162b2 messenger RNA COVID-19 vaccine [ 5 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our patient undergone emergency bypass vascular surgery due to high risk of lower limb amputation as the complete obstruction of superficial femoral artery was occurred. Based on surgical consultation, her initial platelet count was appropriate for the lower extremity operation (platelet>50×10 9 /L) [ 13 ] and platelet transfusion was inhibited due to immune pathogenicity of the VITT that anti-PF4 antibodies could affect transfused platelets [ 14 ]. Further we avoided to use unfractionated heparin for our patients as the previous studies confirmed that immune complexes of the plasma found by functional cytometry in VITT cases strongly mimic the characteristics of heparin induced thrombocytopenia (HIT) immunogenicity, and administration of heparin could deteriorates VITT [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…"We report a case of a 62-year-old man who developed cerebral venous sinus thrombosis with subarachnoid hemorrhage and concomitant thrombocytopenia, which occurred 13 days after ChA-dOx1 nCov-19 injection. " [2] Among others we may extract the following statements:…”
Section: The Problem Of Context-compatibilitymentioning
confidence: 99%